Embodying Stressful Events: No Difference in Subjective Arousal and Neural Correlates Related to Immersion, Interoception, and Embodied Mentalization - De Coninck, Sarah; Aben, Bart; Van den Bussche, Eva; Mariën, Peter; Van Overwalle, Frank (Frontiers in Behavioral Neuroscience, 2021)
Repetitive thought about oneself, including one’s emotions, can lead to both adaptive and maladaptive effects. Construal level of repetitive self-referential thought might moderate this. During interoception, which engages areas such as the insula, the anterior and/or posterior cingulate cortex and the somatosensory cortex, concrete low level construal self-referential thought is applied, which has been shown to lead to more positive emotions after upsetting events. Contrarily, during immersion, related to neural activity in the default mode network (DMN), abstract high level construal self-referential thought is applied, which is linked to depression. The current study investigated whether the integration of concrete and abstract self-referential thought by means of embodied mentalization leads to less subjective arousal, decreased DMN activity and increased somatosensory activity as compared to immersion, and to more DMN activity as compared to interoception. In the fMRI scanner, participants imagined stressful events while adopting immersion, interoception or embodied mentalization. After each imagined stressful event, participants rated their subjective arousal and how difficult it was to apply the mode of self-referential thought. Results showed that participants felt that immersion was easier to apply than embodied mentalization. However, no differences in subjective arousal or neural activity were found between immersion, interoception and embodied mentalization. Possible reasons for this lack of significant differences are discussed.